Molecular basis of ligand binding and receptor activation at the human A3 adenosine receptor - Liudi Zhang; Jesse I. Mobbs; Felix M. Bennetts; Hariprasad Venugopal; Anh T. N. Nguyen; Arthur Christopoulos; Daan van der Es; Laura H. Heitman; Lauren T. May; Alisa Glukhova; David M. Thal (Nature Communications)
Abstract Adenosine receptors (ARs: A1AR, A2AAR, A2BAR, and A3AR) are crucial therapeutic targets; however, developing selective, efficacious drugs for them remains a significant challenge. Here, we present high-resolution cryo-electron microscopy (cryo-EM) structures of the human A3AR in three distinct functional states: bound to the endogenous agonist adenosine, the clinically relevant agonist Piclidenoson, and the covalent antagonist LUF7602. These structures, complemented by mutagenesis and pharmacological studies, reveal an A3AR activation mechanism that involves an extensive hydrogen bond network from the extracellular surface down to the orthosteric binding site. In addition, we identify a cryptic pocket that accommodates the N6-iodobenzyl group of Piclidenoson through a ligand-dependent conformational change of M1745.35. Our comprehensive structural and functional characterisation of A3AR advances our understanding of adenosine receptor pharmacology and establishes a foundation for developing more selective therapeutics for various disorders, including inflammatory diseases, cancer, and glaucoma.